Relationship between Perioperative Hypotension and Perioperative Cardiovascular Events in Patients with Coronary Artery Disease Undergoing Major Noncardiac Surgery. (May 2019) - Roshanov, Pavel S.; Sheth, Tej; Duceppe, Emmanuelle; Tandon, Vikas; Bessissow, Amal; Chan, Matthew T. V.; Butler, Craig; Chow, Benjamin J. W.; Khan, James S.; Devereaux, P. J.
Editor's Perspective: What We Already Know about This Topic: Perioperative hypotension is associated with cardiovascular events in patients having noncardiac surgery, but it is unknown if the severity of preexisting coronary artery disease determines susceptibility to the cardiovascular risks of perioperative hypotension What This Article Tells Us That Is New: In patients who had risk factors for, or known, coronary artery disease and were having noncardiac surgery, perioperative hypotension and degree of coronary artery disease on preoperative coronary computed tomographic angiography were independently associated with perioperative cardiovascular death and myocardial infarction Perioperative hypotension was associated with cardiovascular events regardless of the degree of coronary artery disease on preoperative coronary computed tomographic angiography Background: Perioperative hypotension is associated with cardiovascular events in patients having noncardiac surgery. It is unknown if the severity of preexisting coronary artery disease determines susceptibility to the cardiovascular risks of perioperative hypotension. Methods: In this retrospective exploratory analysis of a substudy of an international prospective blinded cohort study, 955 patients 45 yr of age or older with history or risk factors for coronary artery disease underwent coronary computed tomographic angiography before elective inpatient noncardiac surgery. The authors evaluated the potential interaction between angiographic findings and perioperative hypotension (defined as systolic blood pressure less than 90 mmHg for a total of 10 min or more during surgery or for any duration after surgery and for which intervention was initiated) on the composite outcome of time to myocardial infarction or cardiovascular death up to 30 days after surgery. Angiography assessors were blinded to study outcomes; patients, treating clinicians, and outcome assessors were blinded to angiography findings. Results: Cardiovascular events (myocardial infarction or cardiovascular death within 30 days after surgery) occurred in 7.7% of patients (74/955), including in 2.7% (8/293) without obstructive coronary disease or hypotension compared to 6.7% (21/314) with obstructive coronary disease but no hypotension (hazard ratio, 2.51; 95% CI, 1.11 to 5.66; P = 0.027), 8.8% (14/159) in patients with hypotension but without obstructive coronary disease (hazard ratio, 3.85; 95% CI, 1.62 to 9.19; P = 0.002), and 16.4% (31/189) with obstructive coronary disease and hypotension (hazard ratio, 7.34; 95% CI, 3.37 to 15.96; P < 0.001). Hypotension was independently associated with cardiovascular events (hazard ratio, 3.17; 95% CI, 1.99 to 5.06; P < 0.001). This association remained in patients without obstructive disease and did not differ significantly across degrees of coronary disease ( P value for interaction, 0.599). Conclusions: In patients having noncardiac surgery, perioperative hypotension was associated with cardiovascular events regardless of the degree of coronary artery disease on preoperative coronary computed tomographic angiography. Abstract : In patients who had risk factors for, or known, coronary artery disease and were having noncardiac surgery, perioperative hypotension and degree of coronary artery disease on preoperative coronary computed tomographic angiography were independently associated with perioperative cardiovascular death and myocardial infarction. Perioperative hypotension was associated with cardiovascular events regardless of the degree of coronary artery disease on preoperative coronary computed tomographic angiography.Supplemental Digital Content is available in the text.